Math appeal : mind-stretching math riddles - Tang, Greg.; Briggs, Harry (New York : Scholastic Press, 2003)
Rhyming anecdotes present opportunities for simple math activities and hints for solving.
Booklist
School Library Journal
Wilson's Children
Booklist, February 2003
Christian Library, June 2003
Horn Book, October 2003
Keywords: Mathematics -- Juvenile literature; Mathematical recreations; Mathematics; Mathematical recreations; Mathematics